2015
DOI: 10.1308/003588415x14181254790202
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography alone can reliably locate parathyroid tumours and facilitates minimally invasive parathyroidectomy

Abstract: INTRODUCTION Minimally invasive parathyroidectomy (MIP) is performed via a short incision (≤3cm). Previous studies have employed multiple imaging modalities including ultrasonography, sestamibi imaging and/or intraoperative parathyroid hormone assay. We present our eight-year experience of MIP using ultrasonography alone. METHODS One hundred parathyroidectomies performed by a single surgeon between April 2004 and December 2012 were identified in a prospectively maintained database. All patients underwent ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…However, treatment for benign parathyroid lesions differ from parathyroid carcinoma in that minimally invasive surgery often suffices in adenomas and hyperplasia whilst radical neck surgery is required to treat carcinoma. [9][10][11] Critically, the prognosis of parathyroid carcinoma depends on the removal of the whole lesion as well as nodal clearance at the first surgical procedure. Therefore, it would be advantageous to raise suspicion of a malignant parathyroid lesion prior to surgery, allowing appropriate surgical planning and, importantly, advising the patient of the consequences of more radical surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, treatment for benign parathyroid lesions differ from parathyroid carcinoma in that minimally invasive surgery often suffices in adenomas and hyperplasia whilst radical neck surgery is required to treat carcinoma. [9][10][11] Critically, the prognosis of parathyroid carcinoma depends on the removal of the whole lesion as well as nodal clearance at the first surgical procedure. Therefore, it would be advantageous to raise suspicion of a malignant parathyroid lesion prior to surgery, allowing appropriate surgical planning and, importantly, advising the patient of the consequences of more radical surgery.…”
Section: Introductionmentioning
confidence: 99%
“…It is also critical in patients with minimally invasive parathyroid surgery and focused parathyroidectomy to replace the traditional 4‐gland parathyroid exploration. The success rate of this approach is determined by studies localizing the lesions and confirming normal parathyroid glands, allowing for curative treatment and potentially minimizing the need for extensive intraoperative exploration …”
mentioning
confidence: 99%
“…It should be noted that the overall sensitivity reported in this series of 71% for SPECT/CT is lower than has been reported in meta-analysis, likely due to the low rate of 20 mAs. In contrast, Butt et al [37] described their experience of using US alone and noted that is correctly identified the parathyroid adenoma in 98% of cases suitable for targeted parathyroidectomy.…”
Section: Ultrasound or Scintigraphy?mentioning
confidence: 97%